UPAYA-UPAYA KEPALA MADRASAH DALAM MENINGKATKAN KEDISIPLINAN MENGAJAR GURU RUMPUN PAI - Pip Sumardi (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
Abstract: The results of this study is the condition of the discipline teacher of Islamic education clump at this time there is an increase in teaching, with the holding of the efforts of coaching by the school principal. Constraints head Madrasah in improving the discipline of teachers to teach there must be constraints such as feeling uncomfortable if reprimand teachers who lack discipline or fear of offense, and so on, but according to head Madrasah is not the reason the head of Madrasah in improving the discipline of teachers in teaching, the head of Madrasah continue to work with ways to improve the discipline until the teacher would beruba. Efforts head Madrasah in improving teachers’ teaching discipline clump PAI is as follows. Principals always provide direction and guided to all the teachers in the Mts. State Kertapati Central Bengkulu include: Addressing at the meeting, ask for help with the deputy head of the Madrasah for coaching, the approach to the teacher, then head of the Madrasah also always include the teachers clump PAI for megikuti training or worksop, then the last resort is to report to the supervisor Madrasah, then keKemenag District reported that moved redeployed.